A High‐Pressure NMR Probe for Aqueous Geochemistry1. Issue 37 (2nd July 2014) - Pautler, Brent G.; Colla, Christopher A.; Johnson, Rene L.; Klavins, Peter; Harley, Stephen J.; Ohlin, C. André; Sverjensky, Dimitri A.; Walton, Jeffrey H.; Casey, William H.
Abstract A non‐magnetic piston‐cylinder pressure cell is presented for solution‐state NMR spectroscopy at geochemical pressures. The probe has been calibrated up to 20 kbar using in situ ruby fluorescence and allows for the measurement of pressure dependencies of a wide variety of NMR‐active nuclei with as little as 10 μL of sample in a microcoil. Initial 11B NMR spectroscopy of the H3BO3–catechol equilibria reveals a large pressure‐driven exchange rate and a negative pressure‐dependent activation volume, reflecting increased solvation and electrostriction upon boron‐catecholate formation. The inexpensive probe design doubles the current pressure range available for solution NMR spectroscopy and is particularly important to advance the field of aqueous geochemistry.